2023
DOI: 10.1073/pnas.2211947120
|View full text |Cite
|
Sign up to set email alerts
|

Mechanoepigenetic regulation of extracellular matrix homeostasis via Yap and Taz

Abstract: Cells integrate mechanical cues to direct fate specification to maintain tissue function and homeostasis. While disruption of these cues is known to lead to aberrant cell behavior and chronic diseases, such as tendinopathies, the underlying mechanisms by which mechanical signals maintain cell function are not well understood. Here, we show using a model of tendon de-tensioning that loss of tensile cues in vivo acutely changes nuclear morphology, positioning, and expression of catabolic gene programs, resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 71 publications
0
1
0
Order By: Relevance
“…[ 63,64 ] In fact, a recent study precisely described how the loss of cell tension quickly changes chromatin configuration, downplaying the action of Hippo‐members YAP/TAZ, while YAP overexpression counterbalances this effect. [ 65 ] These data support the previous notion that providing encapsulated stem cells with a biomimetic physical cue is likely to be essential in guiding their path toward tenogenesis by modulating their gene expression patterns. [ 55–58 ] Importantly, the viability of encapsulated hASC was not negatively affected by sMRF and MINP contents within tenogenic constructs, as assessed by LIVE/DEAD staining at both early (day 1) and later (day 7) timepoints (Figure 3G), with viable cells representing over 94% of the total number of cells in all conditions (Figure S9, Supporting Information).…”
Section: Resultssupporting
confidence: 86%
“…[ 63,64 ] In fact, a recent study precisely described how the loss of cell tension quickly changes chromatin configuration, downplaying the action of Hippo‐members YAP/TAZ, while YAP overexpression counterbalances this effect. [ 65 ] These data support the previous notion that providing encapsulated stem cells with a biomimetic physical cue is likely to be essential in guiding their path toward tenogenesis by modulating their gene expression patterns. [ 55–58 ] Importantly, the viability of encapsulated hASC was not negatively affected by sMRF and MINP contents within tenogenic constructs, as assessed by LIVE/DEAD staining at both early (day 1) and later (day 7) timepoints (Figure 3G), with viable cells representing over 94% of the total number of cells in all conditions (Figure S9, Supporting Information).…”
Section: Resultssupporting
confidence: 86%
“…Potentially complicating this aberrant fibroblast activation in the fibrotic lung, there is an increase in stretch response as the lung stiffens during fibrotic remodeling, and fibroblast-focused studies have shown that Yap/Taz are activated in the presence of mechanical stretch ( 24 26 , 45 ). Additional recent findings have shown that Yap/Taz activation is involved in a stretch-associated modulation of chromatin remodeling ( 46 ) by the extracellular matrix, raising the possibility that failure of alveolar epithelial repair alters the local mechanical environment to promote Yap/Taz activation in alveolar fibroblasts and/or that adjacent alveolar epithelial cells to promote tissue fibrosis could generate a feed-forward mechanism. Yap/Taz have also been shown to interact with several other pathways that have been implicated in promoting fibrosis, including TGF-β ( 47 , 48 ), Wnt ( 49 52 ), FGF ( 53 ), Notch ( 54 ), and mTOR/Pi3K ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…While there is no evidence of regulation of MMPs by YAP in the lens upon induction by TGFβ, knockdown of YAP using siRNA results in upregulation of MMP2 in mammary epithelial cancer cells [41]. In contrast, a recent report found positive changes in chromatin accessibility at genomic loci, resulting in upregulation of MMP2, MMP3, MMP10, MMP13, and MMP14 in connective tissue cells over-expressing constitutively active YAP [60]. In agreement with the later findings, we observed a significant downregulation of TGFβ-induced MMP2 expression in LECs upon YAP inhibition when compared to LECs treated with TGFβ alone (Figure 6).…”
Section: Discussionmentioning
confidence: 92%